2003
DOI: 10.1159/000070853
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Vagus Nerve Stimulation for Intractable Epilepsy: Is Seizure Control the Only Contributing Factor?

Abstract: We assessed the impact of vagus nerve stimulation on a cohort of patients with intractable epilepsy. A 1-year prospective trial of vagus nerve stimulation for intractable epilepsy was done in 26 patients. Seizure frequency, anti-epileptic drugs, and quality of life were assessed using QOLIE-89, ELDQOL, and a Likert scale of impact of treatment. Seizures were reduced by more than 50% in 19% of the patients, by less than 50% in 46%, and were unchanged in 35% of them. Antiepileptic drugs were reduced in 43% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
3
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 5 publications
4
29
3
4
Order By: Relevance
“…19,20 Moreover, in previous studies, VNS-associated improvement in QOLIE-89 score and other measures of quality of life did not correlate with changes in seizure frequency. 21 Finally, our HRQoL findings do not seem to be primarily driven by an effect of VNS on mood, because no significant differences were observed between VNS + BMP and BMP groups in the two depression scales used in this study (CES-D and NDDI-E), or in the QOLIE-89 Mental Health subscale. Based on these findings, we suggest that the VNS-related improvement in HRQoL in our patients might reflect the sum of modest benefits in multiple factors rather than a single determinant.…”
Section: Discussionmentioning
confidence: 55%
“…19,20 Moreover, in previous studies, VNS-associated improvement in QOLIE-89 score and other measures of quality of life did not correlate with changes in seizure frequency. 21 Finally, our HRQoL findings do not seem to be primarily driven by an effect of VNS on mood, because no significant differences were observed between VNS + BMP and BMP groups in the two depression scales used in this study (CES-D and NDDI-E), or in the QOLIE-89 Mental Health subscale. Based on these findings, we suggest that the VNS-related improvement in HRQoL in our patients might reflect the sum of modest benefits in multiple factors rather than a single determinant.…”
Section: Discussionmentioning
confidence: 55%
“…13,18,27,28,31,54 Moreover, numerous studies found that VNS can benefit attention, cognition, behavior, mood, and quality of life independent of reduced seizure burden. 1,22,24,25,35,41 These findings suggest that consideration of VNS earlier in the course of refractory disease is warranted. 42 No randomized studies have demonstrated long-term benefits of VNS therapy on cognitive, social, or behavioral development or quality of life.…”
Section: Seizure Control and Developmentmentioning
confidence: 97%
“…Indeed, a 1-year prospective trial of VNS for intractable epilepsy showed significant improvement in mean overall QOL, and subjective improvement was found in 84% of the 26 patients studied. 47 After exiting the blinded portion of these trials, patients were followed for up to 18 months, all of whom received therapeutic levels of VNS, given the apparent therapeutic benefit. 15,48,49 Mean seizure frequency percent change was significant for all follow-up periods of VNS, relative to baseline.…”
mentioning
confidence: 99%